(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
هدفت هذه الدراسة إلى تحديد الهوية الوراثية لأصول الحمضيات العشرة الموجودة في مجمع الأصول الوراثية في قسم بحوث الحمضيات في طرطوس، باستخدام مؤشرات التوابع الدقيقة المتكررة SSR . تم تحليل إحدى وثلاثين عينة (31 مدخلاً) من الـحمض النووي منقوص الأوكسجين ((DNA باستخدام سبعة عشر زوجاً من البادئات، ثم أجريت مقارنة نتائج المكاثرة والتعرف على القرائن المتعددة على المواقع المختلفة، و من ثم تم تحديد قرائن معينة قادرة على التمييز بين أغلب الأصول المدروسة. قدر البعد الوراثي بين المدخلات المدروسة, واستخدمت المعطيات في إنشاء شجرة القرابة الوراثية بين الأصول العشرة. بينت النتائج أن الأصلين كاريزو سيترانج وستروميللو هما الأكثر قرباً للبرتقال ثلاثي الأوراق، حيث تجمعوا معاً في مجموعة واحدة منفصلة عن بقية الأصول، مدعماً للفكرة التي تشير إلى أن البرتقال ثلاثي الاوراق هو أحد الآباء المشاركة في إنتاج هذه الأصول. أظهرت النتائج أن جميع مدخلات الأصل الواحد كانت متشابهة وتجمعت مع بعضها في فرع واحد منفصل عن أفرع مدخلات الأصول الأخرى، وان أعلى نسبة للتنوع الوراثي قد سجلت في الليم الفلسطيني و النارنج وأقلها في البرتقال ثلاثي الأوراق، كما لوحظت حالة غياب النقاوة الوراثية في جميع الأصول المدروسة. The objectives of this study are the genetic identification of ten Citrus rootstocks, present in the germplasm pool at the Department of Citrus Research in Tartous, using microsatellite markers (SSR). Thirty-one DNA samples (31 accesssions) were analyzed using 17 SSR primer pairs. The amplified products were compared and the different alleles were identified at the different loci. Specific alleles were detected in some genotypes, allowing the distinction between the studied rootstocks. Alleles amplified by SSR primers were scored and data was used to evaluate the genetic distance and to establish a dendrogram of genetic relationships between the 10 rootstocks. The results showed that Carrizo citrange and Citromello were the closest rootstocks to trifoliate orange and were regrouped in a cluster, distant from the other genotypes, which supports the idea that Trifoliate is one of the parents involved in the production of these two rootstocks. All accessions of one rootstock were regrouped in one branch. The highest value of genetic diversity was detected in Lime and Sour orange, while the lowest one was detected in Trifoliate orange. The genetic impurity was detected in all studied rootstocks.